Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - Obura, David O.; Aeby, Greta; Amornthammarong, Natchanon; Appeltans, Ward; Bax, Nicholas; Bishop, Joe; Brainard, Russell E.; Chan, Samuel; Fletcher, Pamela; Gordon, Timothy A. C.; Gramer, Lew; Gudka, Mishal; et al. (Frontiers in Marine Science, 2019)
Coral reefs are exceptionally biodiverse, and human dependence on their ecosystem services is high. Reefs experience significant direct and indirect anthropogenic pressures, and provide a sensitive indicator of coastal ocean health, climate change and ocean acidification, with associated implications for society. Monitoring coral reef status and trends is essential to better inform science, management and policy, but the projected collapse of reef systems within a few decades makes the provision of accurate and actionable monitoring data urgent. The Global Coral Reef Monitoring Network has been the foundation for global reporting on coral reefs for two decades, and is entering into a new phase with improved operational and data standards incorporating the Essential Ocean Variables (EOVs) (www.goosocean.org/eov) and Framework for Ocean Observing developed by the Global Ocean Observing System. Three EOVs provide a robust description of reef health: hard coral cover and composition, macro-algal canopy cover, and fish diversity and abundance. A data quality model based on comprehensive metadata is designed to facilitate maximum global coverage of coral reef data, and tangible steps to track capacity building. Improved monitoring of events such as mass bleaching and disease outbreaks, citizen science and socio-economic monitoring have the potential to greatly improve the relevance of monitoring to managers and stakeholders, and to address the complex and multi- dimensional interactions between reefs and people. XX THERE IS SOMETHING WRONG IN THE ABSTRACT WORD LIMIT, ONE MORE PARAGRAPH WAS INCLUDED IN THE ORIGINAL TEXT!!